Systemic inflammation mediates the association between the dietary index for gut microbiota and serum Klotho: evidence from NHANES 2007–2016 - Lv, Xintao; Liu, Heng; Zhou, Yu; Hao, Haidong; Yuan, Yutang; Jia, Hongtao; Jin, Mingchu (Frontiers in Nutrition, 2025)
BackgroundThe Dietary Index for Gut Microbiota (DI-GM) is a novel dietary assessment tool reflecting the impact of diet on gut microbiota composition. Serum Klotho, an anti-aging protein, has been implicated in various metabolic and inflammatory processes. However, the relationship between the DI-GM Score and serum Klotho levels, as well as the potential mediating role of inflammatory markers, remains unclear. This study aims to investigate the association between DI-GM and serum Klotho and to explore the mediating effect of systemic inflammation.MethodsThis cross-sectional study utilized data from the 2007–2016 National Health and Nutrition Examination Survey (NHANES). Participants aged 40–79 years were included, and a total of 12,341 individuals remained after applying exclusion criteria. The DI-GM Score was calculated based on dietary intake data, while serum Klotho levels were measured using ELISA. The systemic immune-inflammation index (SII) and systemic inflammation response index (SIRI) were derived from complete blood counts to assess inflammation. Multivariate linear regression models, restricted cubic spline (RCS) analysis, subgroup analysis, and mediation analysis.ResultsDI-GM Score was positively associated with serum Klotho levels after adjusting for confounders (β = 4.05, 95% CI: 1.31, 6.80, p = 0.004). Compared to participants with the lowest DI-GM scores (0–3), those with DI-GM ≥ 6 had significantly higher serum Klotho levels (β = 21.65, 95% CI: 8.14, 35.17, p = 0.002). RCS analysis confirmed a linear positive relationship. Subgroup analysis indicated a stronger association in non-drinkers (p for interaction < 0.05). Mediation analysis revealed that SII and SIRI partially mediated the relationship between DI-GM and serum Klotho, with mediation proportions of 7.15% and 5.68%, respectively.ConclusionA higher DI-GM Score is significantly associated with increased serum Klotho levels among middle-aged and older adults, with systemic inflammation serving as a partial mediator. These findings suggest that dietary patterns promoting gut microbiota health may enhance Klotho levels, potentially contributing to anti-inflammatory and anti-aging processes in this population.